Interaction of L-Phenylalanine with a Phospholipid Monolayer at the Water-Air Interface - Griffith, Elizabeth C; Perkins, Russell J; Telesford, Dana-Marie; Adams, Ellen M; Cwiklik, Lukasz; Allen, Heather C; Roeselová, Martina; Vaida, Veronica (The journal of physical chemistry. B, 2015)
The interaction of L-phenylalanine with a 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) monolayer at the air-water interface was explored using a combination of experimental techniques and molecular dynamics (MD) simulations. By means of Langmuir trough methods and Brewster angle microscopy, L-phenylalanine was shown to significantly alter the interfacial tension and the surface domain morphology of the DPPC film. In addition, confocal microscopy was used to explore the aggregation state of L-phenylalanine in the bulk aqueous phase. Finally, MD simulations were performed to gain molecular-level information on the interactions of L-phenylalanine and DPPC at the interface. Taken together, these results show that L-phenylalanine intercalates into a DPPC film at the air-water interface, thereby affecting the surface tension, phase morphology, and ordering of the DPPC film. The results are discussed in the context of biological systems and the mechanism of diseases such as phenylketonuria.
Keywords: Air; Deuterium; Molecular Structure; simulace molekulární dynamiky; 1,2-Dipalmitoylphosphatidylcholine; Water; fenylalanin; deuterium; povrchové vlastnosti; Microscopy; Phenylalanine; vzduch; Molecular Dynamics Simulation; 1,2-dipalmitoylfosfatidylcholin; mikroskopie; voda; molekulární struktura; Surface Properties